Molecular Mechanisms of Action of Emodin: As an Anti-Cardiovascular Disease Drug - Li, Qianqian; Gao, Jian; Pang, Xiaohan; Chen, Aiping; Wang, Yi (Frontiers in Pharmacology, 2020)
Emodin is a natural occurring anthraquinone derivative isolated from roots and barks of numerous plants, molds, and lichens. It is found to be an active ingredient in different Chinese herbs including Rheum palmatum and Polygonam multiflorum, and it is a pleiotropic molecule with diuretic, vasorelaxant, anti-bacterial, anti-viral, anti-ulcerogenic, anti-inflammatory, and anti-cancer effects. Moreover, emodin has also been shown to have a wide activity of anti-cardiovascular diseases. It is mainly involved in multiple molecular targets such as inflammatory, anti-apoptosis, anti-hypertrophy, anti-fibrosis, anti-oxidative damage, abnormal and excessive proliferation of smooth muscle cells in cardiovascular diseases. As a new type of cardiovascular disease treatment drug, emodin has broad application prospects. However, a large amount of evidences detailing the effect of emodin on many signaling pathways and cellular functions in cardiovascular disease, the overall understanding of its mechanisms of action remains elusive. In addition, by describing the evidence of the effects of emodin in detail, the toxicity and poor oral bioavailability of mice have been continuously discovered. This review aims to describe a timely overview of emodin related to the treatment of cardiovascular disease. The emphasis is to summarize the pharmacological effects of emodin as an anti-cardiovascular drug, as well as the targets and its potential mechanisms. Furthermore, the treatment of emodin compared with conventional cardiovascular drugs or target inhibitors, the toxicity, pharmacokinetics and derivatives of emodin were discussed.